2019
DOI: 10.1097/dss.0000000000001726
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Combining Fractional Carbon Dioxide Laser With Verapamil Hydrochloride or 5-Fluorouracil in the Treatment of Hypertrophic Scars and Keloids: A Clinical and Immunohistochemical Study

Abstract: BACKGROUND Ablative fractional laser-assisted therapy is increasingly used to facilitate drug delivery and intensify clinical efficacy of topically applied drugs. OBJECTIVE To evaluate the effectiveness of combined ablative fractional CO2 laser and topically applied 5-fluorouracil (5-FU) or verapamil hydrochloride in the treatment of hypertrophic scars (HTSs) and keloids and to examine their possible effects on TGF-β1 expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…The study of Sabry et al 17 reported that the VSS significantly reduced 1 month following the last treatment session in all cases (P < .05).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The study of Sabry et al 17 reported that the VSS significantly reduced 1 month following the last treatment session in all cases (P < .05).…”
Section: Discussionmentioning
confidence: 83%
“…The study of Sabry et al 17 subjected 30 cases suffering from HTSs and keloids to a monthly dose of one of the following treatment regimens for four successive months; (CO 2 laser alone or CO 2 laser followed by topical verapamil or 5‐flurouracil application) and reported that the VSS significantly reduced 1 month following the last treatment session in all cases ( P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several medications have been reported for laser-assisted drug delivery for keloids and hypertrophic scars and include verapamil hydrochloride, 3 5-fluorouracil,3, 4 and steroids 4, 5, 6, 7, 8. Different vehicles of steroids have been used following laser treatments (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…While pain reduction was significantly higher in the CO 2 laser group, the authors largely found that these two treatments are equivalent [68]. Sabry et al found that the combination of CO 2 laser with either topical verapamil or 5-fluorouracil was more efficacious than laser alone, with no adverse effects [69]. A randomized controlled trial evaluating intralesional cryotherapy as compared to excision and steroid or excision and brachytherapy performed by Bijlard et al was stopped because of significantly inferior results in the intralesional cryotherapy group.…”
Section: Comparisonsmentioning
confidence: 99%